Political Commissive Speech Act on Susilo Bambang Yudhoyono’s Speech towards Wire-Tapping - Widianingsih, Ayang Winda Sri; Pratama, Shadam Hussaeni Handi (STAIN Sultan Abdurrahman Kepulauan Riau, 2023)
This study focuses on Susilo Bambang Yudhoyono's speech, the President of Indonesia from 2004 – 2014, who gave a speech about wire-tapping. This research project chooses this speech because, in recent days, wire-tapping, which Australia does, is famous. Moreover, the president at that time, Susilo Bambang Yudhoyono, was one of the wire-tapped victims. It was hot news for Indonesian at that time. On November 2013, SBY gave a speech about his action regarding this wiretapping. Thus, this paper analyzes the commissive speech act and its function. To explain the text clearly, a pragmatic analysis will be employed. This approach is used because the study intends to see the function of commissive speech acts beyond the text; therefore, some information will be scientifically proved regarding the act and its functions. This analysis is based on (Searle, 1969). The result of the study is expected to reveal the aforementioned intended information.